2017
DOI: 10.5539/mas.v11n5p47
|View full text |Cite
|
Sign up to set email alerts
|

An Eco-Friendly Process for Removal of Lead from Aqueous Solution

Abstract: The adsorption of lead (Pb II) ion on different types of synthesized zeolite was investigated. The BET surface area, total pore volume & average pore size distribution of these synthesized zeolites were determined by adsorption isotherms for N2, the surface area & total pore volume of their sources were found by adsorption isothermN2.The adsorption equilibrium was measured after 24h at room temperature ( The atomic absorption spectrometry was used for analysis of lead heavy metal ion, the obtained results in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…As a result, size of surface area and pore volume of ZCF had higher than ZBG whereas the pore size of ZBG had larger than ZCF. The previous studies reported that zeolite A materials exhibited the high surface area and pore volume with a small pore size resulted to the high adsorption capability [ 58 , 59 ], so it was possible that ZCF was higher lead adsorption than ZBG. For STD, size of surface area, pore volume, and pore size were 10.460 m 2 /g, 0.030 cc/g, and 49.020 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, size of surface area and pore volume of ZCF had higher than ZBG whereas the pore size of ZBG had larger than ZCF. The previous studies reported that zeolite A materials exhibited the high surface area and pore volume with a small pore size resulted to the high adsorption capability [ 58 , 59 ], so it was possible that ZCF was higher lead adsorption than ZBG. For STD, size of surface area, pore volume, and pore size were 10.460 m 2 /g, 0.030 cc/g, and 49.020 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of X-ray diffraction patterns for synthesized samples (Fig. 3) shows that all catalysts have a crystalline structure corresponding to the structure of MOR zeolite (JCPDS Card # 29-1257) [24]. XRD Three characteristic peaks for nickel (2q = 44.5°, 51.8°, and 76.4°), corresponding to Miller indices (111), (200), and (222), are also shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Isotherms are typical ones for micro/mesoporous sorbents, which are characterized by a steep rise at low P/P s values assigned to the formation of equilibrium Langmuir adsorbate monolayers and a hysteresis loops over higher P/P s values [21][22][23][24]. Isotherms belong to IVa type with H3 hysteresis loop according to the classification of IUPAC [21], and this could be related to cylindrical pore channels.…”
Section: Resultsmentioning
confidence: 99%